Business missions for Export Development - Eshmamatova Madina (International Journal on Human-Computing Studies, 2021)
Marketing tools, like weapons, can be divided into two large groups. This can be both in advertising campaigns, and in personal contacts, to meet with the" counterparty " face to face. As often happens in such situations, there are various intermediate, less frequently used, but also more effective "types of weapons". Such hybrid forms. For marketing, a good example is business missions. How the participant understands that this tool works in the market also determines its effectiveness - the volume of sales and the number of new counterparties